Capital Structure Choices and Behavioral Biases: An Application to a Panel of US Industrial Companies - Esghaier, Ridha (International Journal of Economics and Financial Issues, 2017)
This paper examines the financing decision within the framework of the behavioral corporate finance. It empirically analyzes the role of psychological factors related to the managers' overconfidence and optimism in explaining the financing choices of a panel of 160 US industrial companies listed over the period from 2009 to 2015. Our findings confirm the positive and significant impact of managers' overconfidence and optimism on the leverage of their firms. Our tests also highlight the negative and significant impact of the market mispricing perceived by the manager on the debt level of his firm, supporting its market timing behavior. A non-less interesting final result concerns the positive impact of managers' overconfidence on their pecking order preferences, thus rejecting the theoretical hypothesis under which the managers' overconfidence leads to a reverse pecking order preference over the financing sources. Keywords: Capital structure; optimism; overconfidence; market timing; pecking order. JEL Classifications: G32, C23